Rapid evolution of a floral trait following acquisition of novel pollinators - Mackin, Christopher R. (2021)
1. Changes in the pollinator assemblage visiting a plant can have consequences for reproductive success and floral evolution. We studied a recent plant trans-continental range expansion to test whether the acquisition of new pollinator functional groups can lead to rapid adaptive evolution of flowers. 2. In Digitalis purpurea, we compared flower visitors, floral traits and natural selection between native European populations and those in two Neotropical regions, naturalised after independent introductions. Bumblebees are the main pollinators in native populations while both bumblebees and hummingbirds are important visitors in the new range. We confirmed that the birds are effective pollinators and deposit more pollen grains on stigmas than bumblebees. 3. We found convergent changes in the two new regions towards larger proximal corolla tubes, a floral trait that restricts access to nectar to visitors with long mouthparts. There was a strong positive linear selection for this trait in the introduced populations, particularly on the length of the proximal corolla tube, consistent with the addition of hummingbirds as pollinators. 4. Synthesis. The addition of new pollinators is likely to happen often as humans influence the ranges of plants and pollinators but it is also a common feature in the long-term evolution of the angiosperms. We show how novel selection followed by very rapid evolutionary change can be an important force behind the extraordinary diversity of flowers.